0.5 V Versatile Voltage- and Transconductance-Mode Analog Filter Using Differential Difference Transconductance Amplifier - Kulej, Tomasz; Kumngern, Montree; Khateb, Fabian; Arbet, Daniel (My University, 2023)
In this work, a new versatile voltage- and transconductance-mode analog filter is proposed. The filter, without requiring resistors, employs three differential-difference transconductance amplifiers (DDTAs) and two grounded capacitors, which is suitable for integrated circuit implementation. Unlike previous works, the proposed filter topology provides: (1) high-input and low-output impedances for a voltage-mode (VM) analog filter, that is desirable in a cascade method of realizing higher order filters, and (2) high-input and high-output impedances for a transconductance-mode (TM) analog filter without any circuit modification. Moreover, a quadrature oscillator is obtained by simply adding a feedback connection. Both VM and TM filters provide five standard filtering responses such as low-pass, high-pass, band-pass, band-stop and all-pass responses into single topology. The natural frequency and the condition of oscillation can be electronically controlled. The circuit operates with 0.5 V supply voltage. It was designed and simulated in the Cadence program using 0.18 µm CMOS technology from TSMC.
Keywords: analog circuit; analog filter; differential different transconductance amplifiers (DDTA); oscillator